Extreme Outcomes Sway Risky Decisions from Experience. (11th July 2013) - Ludvig, Elliot A.; Madan, Christopher R.; Spetch, Marcia L.
ABSTRACT Whether buying stocks or playing the slots, people making real‐world risky decisions often rely on their experiences with the risks and rewards. These decisions, however, do not occur in isolation but are embedded in a rich context of other decisions, outcomes, and experiences. In this paper, we systematically evaluate how the local context of other rewarding outcomes alters risk preferences. Through a series of four experiments on decisions from experience, we provide evidence for an extreme‐outcome rule, whereby people overweight the most extreme outcomes (highest and lowest) in a given context. As a result, people should be more risk seeking for gains than losses, even with equally likely outcomes. Across the experiments, the decision context was varied so that the same outcomes served as the high extreme, low extreme, or neither. As predicted, people were more risk seeking for relative gains, but only when the risky option potentially led to the high‐extreme outcome. Similarly, people were more risk averse for relative losses, but only when the risky option potentially led to the low‐extreme outcome. We conclude that in risky decisions from experience, the biggest wins and the biggest losses seem to matter more than they should. Copyright © 2013 John Wiley & Sons, Ltd.